MIKROZONASI KERENTANAN BAHAYA GONCANGAN GEMPA BUMI KOTA PEKALONGAN BERDASARKAN ANALISIS MIKROTREMOR - Soehaimi, Asdani; Marjiono, Marjiono; Kamawan, Kamawan (Pusat Survei Geologi, 2010)
Microzonation of Pekalongan is divided into 3 zones: Ground shaking prone zone I, characterized by very high amplification (>9 times), 0.93 – 1.15 second dominant period and soft sediment thickness between of 40.14 – 50.29 m; ground shaking prone zone II, characterized by high amplification (6-9 times), 0.55 – 1.49 second dominant period of second and soft sediment thickness between 23.91 – 65.30 m; ground shaking prone zone III, characterized by intermediate amplification (3-6 times), 0.47 – 1.54 second dominant period, and soft sediment thickness between 20.73 – 67.31 m.In generall, Pekalongan has amplification between 3, 17 – 12, 91 times. More than 50 % of its area has high amplification, some small spots/areas have very high amplification, and the rest area have intermediate amplification.Microzonation is as the preliminary step for earthquake risk mitigation efforts.In order to reduce the hazard risk, the local government must have policies on spatial planning. Regions which have high – very high amplification need to be developed with specific construction.Keywords: Pekalongan, microzoantion, amplification and predominant period